Menggali Makna Kerja Dalam Konteks Ajaran Sosial Gereja Ditinjau Dari Perspektif Ensiklik Laborem Exercens - Viktoria Stela Reyaan; Teresia Noiman Derung (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2025)
This research aims to explore the meaning of work in the context of the Church's social teachings, with a focus on the perspective of the encyclical Laborem Exercens.The background to this research is rooted in the importance of understanding work as an integral part of human life and Church teachings. The method used is qualitative analysis of the encyclical, which includes text study and interpretation of meaning. The findings show that work is seen as a deep calling, where each individual contributes to the creation and well-being of society. In addition, this encyclical emphasizes the values ​​of justice, solidarity and human dignity in the world of work. The implication of this research is the need to reaffirm the importance of work ethics based on Church teachings, as well as encouragement to create a more just and humane work environment. It is hoped that the results of this research can become a reference for stakeholders in formulating policies that support the principles of the Church's social teachings in daily work practices.